The Critique of the Book "The Crafters and Their Business Life in the Safavid Period: Essays in the Socio-Economic History of Iran" - Shahram Yousefifar; Ahmad Abohamzeh; Behrang Zolfaghari; Amir Samadi Ahangar; Zahra Ghashghaei Nejad; said najjar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article focuses on the critique of the book "The Crafters and Their Business Life in the Safavid Period: Essays in the Socio-Economic History of Iran" by Mahdi Kavani. This work was considered as the first independent book on the subject. The author influenced the views of the nineteenth-century thinkers of Western Europe, exploring some of the social developments in this age and trying to prove that the Safavid government was preventing the formation of powerful independent autonomous merchants, and consequently, the economic dynamism of this period. This work is organized in six sections and 31 sub-sections. After the first part, which includes the general introduction of the work, the section examines and analyzes the dimension of the effect and then introduces the author and translator. But, the most important part of this review is the background of the research on guilds in Iran and beyond, and analyzing the effect of the content. The latter section is presented in two parts: introspection and outsourcing critique.This critique is the first output of the "Review of the Impact of the Research on Social History" which has been reorganized in the framework of the Council for the Study of Texts and Humanities Books.